The Application of Controlled Writing Technique for Students’ Writing Skill at SMP Yabes School - Dorayanti Lumbangaol; Risma Hartati; Zulmawati; Tiara Pasaribu; Donna Pasaribu (JURNAL ABDIMAS MADUMA, 2022)
Controlled Writing Technique is a technique where students generate, organize, and express their own ideas, in their own sentences. Controlled writing can give benefits at all levels of teaching and not just in the early stages before students have the ability to compose free writing. The aim of this community dedication is to improve the students ability in the writing skills at SMP Yabes School. There are 30 students as participant in this activity. The method that used in this community dedication is by giving training to the students about the application of of controlled Writing technique for the student at SMP Yabes School, before the training was given the first stage the team did is survey the location then give some interview about the problem at the students face at the school. The team found that the students are difficult to understand about writing. after the traning the team of community given the pre-test and post test to the participants then give some quistionare to the students and partners to know about their respond with our community dedication. Based on the result of the pre-test and post test that given to the students, it was found that there was improvement of the average value between the pre-test and the post test on 58,52 %, where the average value of the pre-test was 44,40 and the post-test 75,60 so it can be concluded that the controlled writing technique can improve the students ability in writing. Based on the interview with the partners they convey that the community dedication is very useful to the students and hence the students more interest to study English especially in writing, the partners said that they still waiting for the community in the future. Key Words : Controlled Writing Technique, Writing Skills